The Kathmandu valley : A study in regional geography - Haffner, Willibald; Justus Liebig University Giessen (My University, 1981)
Anyone studying the map of the Kathmandu valley is struck by the almost plastic contrast between the valley bottom and its mountainous, wooded frame dissected by U-shaped valleys. A naturally favourable situation, together with a position that controls the pass of one of the most important trade and pilgrimage routes in the central Himalayas provided decisive impulses for the development of the three largest towns of Nepal: Kathmandu, Pata and Bhaktapur. More than half of the 600.000 inhabitants of the Kathmandu Valley, however, live in smaller rural settlements and have made the irrigated valley bottom the agriculturally most intensively utilised area.

Auf der Karte des Kathmandu-Tals sticht der Kontrast zwischen dem Talgrund und der bergigen, bewaldeten, von U-förmigen Tälern durchzogenen Rändern ins Auge. Die günstige geographische Lage, die die Kontrolle einer der wichtigsten Handels- und Pilgerrouten im Zentralhimalaja ermöglicht, hat einen entscheidenden Impuls zur Entstehung der drei größten Städte in Nepal - Kathmandu, Patan und Bhaktapur - geleistet. Auf der anderen Seite leben mehr als die Hälfte der 600.000 Einwohner in kleineren ländlichen Siedlungen und haben den bewässerten Talgrund zur am landwirtschaftlich intensivsten genutzten Fläche gemacht.
Keywords: Nepal; Kathmandu; Topographie; Nepal; Kathmandu; topography; ddc:910